2006
DOI: 10.1037/0096-1523.32.4.932
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for episodic retrieval of inadequate prime responses in auditory negative priming.

Abstract: Four experiments are reported in which the mechanisms underlying auditory negative priming were investigated. In Experiments 1A and 1B, preprime-prime intervals and prime-probe intervals were manipulated. The ratio between the 2 intervals determined the size of the negative priming effect. Results are compatible with the episodic retrieval account, according to which the retrieval of inappropriate response information associated with the previous distractor slows down responding when that stimulus becomes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
214
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(230 citation statements)
references
References 33 publications
(69 reference statements)
14
214
1
Order By: Relevance
“…It seems that a retrieval of event files can be mediated by perceptual features (e.g., Frings & Rothermund, 2011;Hommel, 2004;Mayr & Buchner, 2006), by word entries in a lexicon (Giesen & Rothermund, 2011;Rothermund et al, 2005), by location information (Frings & Moeller, 2010), and also by conceptual representations of irrelevant stimuli-as evidenced by the results of the present study.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It seems that a retrieval of event files can be mediated by perceptual features (e.g., Frings & Rothermund, 2011;Hommel, 2004;Mayr & Buchner, 2006), by word entries in a lexicon (Giesen & Rothermund, 2011;Rothermund et al, 2005), by location information (Frings & Moeller, 2010), and also by conceptual representations of irrelevant stimuli-as evidenced by the results of the present study.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, the binding of stimuli and responses is not restricted to stimulus features that are relevant for the selection of an action. Recent studies have found that even irrelevant or distracting elements of a situation can become associated with a response given to another object, a phenomenon that has been labeled distractor-response binding (e.g., Frings, 2010;Frings, Rothermund, & Wentura, 2007;Hommel, 2005;Mayr & Buchner, 2006;Mayr, Buchner, & Dentale, 2009;Rothermund, Wentura, & De Houwer, 2005). Distractor-response binding is typically tested with a paradigm where a prime target is presented before a probe target, each one being presented simultaneously with a distractor.…”
mentioning
confidence: 99%
“…For example, in NP experiments from our laboratory using visual selection tasks, the average NP effect size is between dz 0.20 to dz 0.50 (e.g., Frings, 2006;Frings & Wentura, 2006a, 2006bFrings & Wühr, 2007). In contrast, studies using auditory stimuli have produced quite large NP effect sizes, from dz 0.85 to dz 1.08 (Mayr & Buchner, 2006). The reason for these differences in NP, however, might not be a modality-specific effect.…”
Section: Resultsmentioning
confidence: 87%
“…Residual inhibition of the former distractor stimulus results in a disadvantage if a response to this inhibited stimulus is required on the probe 1,11 . On the other hand, negative priming can be the result of retrieval mechanisms 12,13 . For example, Neill assumed that the prime distractor is encoded together with a do-not-respond tag at the prime, which is then retrieved and in turn conflicts with responding to this stimulus if it is repeated as the probe target 14 .…”
Section: Introductionmentioning
confidence: 99%